Between the desire of going global and creating a global team : proposal of a diversity management model, construction of scale and implications - Hämer, Hannah Deborah (2021)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Psicologia, Programa de Pós-Graduação em Psicologia Social, do Trabalho e das Organizações, 2021.